Long term preservation of DNA from honey bees (Apis mellifera) collected in aerial pitfall traps - Rubink, William L. (2010)
This study examines the preservation of nuclear and mitochondrial DNA from honey bee (Apis mellifera L.) specimens which were first kept in propylene glycol-based antifreeze under various conditions, and then stored long-term, refrigerated in 95% ethanol. Two sets of bees were subjected to the propylene glycol treatment, then ethanol storage. One set consisted of bees captured in the field in propylene glycol-containing "aerial pitfall traps", where they remained for up to 21 days. A second set consisted of bees taken from a hive and kept in propylene glycol under various temperature and lighting conditions for up to 90 days. Both the field bees and laboratory bees were then stored long-term in ethanol before evaluation of the persistence of nuclear and mitochondrial DNA using the polymerase chain reaction. DNA integrity was preserved for both field and laboratory specimens. The results demonstrate that propylene glycol-captured, ethanol-preserved honey bees retain both nuclear and mitochondrial DNA after capture and long tern preservation. It is suggested that with little or no modification, the techniques described here might he applied to other studies involving trap-collected arthropod specimens.